A Dual 5α-Reductase Inhibitor Dutasteride Caused Reductions in Vascular Density and Area in Benign Prostatic Hyperplasia. (17th January 2013) - Zaitsu, Masayoshi; Tonooka, Akiko; Mikami, Koji; Hattori, Mami; Takeshima, Yuta; Uekusa, Toshimasa; Takeuchi, Takumi
Abstract : Objectives . Dutasteride, a dual 5 α -reductase inhibitor, is used to treat benign prostatic hyperplasia. Nevertheless, its histopathological effects on the morphometrics of blood vessels and glands are still controversial. The aim here was to assess the histopathological effects of dutasteride in cases of benign prostatic hyperplasia in a retrospective study. Methods . Patients with benign prostatic hyperplasia more than 40 cm 3 in prostatic volume were administered 0.5 mg of dutasteride daily or left untreated prior to receiving a transurethral resection of the prostate. Images of sections stained with hematoxylin/eosin and with anti-CD31 antibody were analyzed. Results . In the dutasteride-treated group, the duration of administration was 16.3 ± 8.1 weeks. Artery/arteriole density and vein/venule density in benign prostatic tissue were both lower in the dutasteride-treated group than in the control group. The vein/venule area as a percentage of the whole area was also lower in the dutasteride-treated group, while the artery/arteriole area did not show a significant difference. Glandular/CD31-expressing vessel densities as well as glandular/CD31-expressing vessel areas were comparable between the two groups. Conclusions . Dutasteride reduced the artery/arteriole and vein/venule densities and the proportion of vein/venule area in the tissue of patients with benign prostatic hyperplasia.